2014
DOI: 10.1148/radiol.14131969
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Primary and Secondary Hepatic Malignancies Associated with Hepatopulmonary Shunting

Abstract: LSF greater than 20% periodically occurs in HCC but is uncommon in other liver tumors. Specific tumor characteristics are associated with LSF greater than 20% and may indicate need for interventions to reduce LSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 24 publications
1
35
2
1
Order By: Relevance
“…(dose reduction advocated), of which 6 were greater than 15% (further reduction) and of which 3 were greater than 20% (contraindication (22). A better estimator of the lung shunt would thus be relevant for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…(dose reduction advocated), of which 6 were greater than 15% (further reduction) and of which 3 were greater than 20% (contraindication (22). A better estimator of the lung shunt would thus be relevant for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure safety, the hepatopulmonary lung shunt fraction (LSF) is calculated in each 90 Y candidate prior to treatment by imaging the distribution of 99m Tc-MAA in the liver and lungs following its delivery within the targeted tissues. 8 Patients with excessive hepatopulmonary shunting may be ineligible for 90 Y or require dose reductions to offset the risk of lung damage. In addition to evaluating safety, current evidence shows that LSF may be associated with advanced disease.…”
mentioning
confidence: 99%
“…In addition to evaluating safety, current evidence shows that LSF may be associated with advanced disease. 8,9 In a study of 23 HCC patients treated with 90 Y, multivariate analysis demonstrated an association between prolonged progression-free survival and low LSF. 10 Considering the functional role of angiogenesis in metastasis, it is possible that LSF may be associated with the risk of metastatic spread of cancer cells from established primary and secondary liver tumors.…”
mentioning
confidence: 99%
“…Planning angiography provides the opportunity for vascular mapping, embolization of variant vascularity to ensure safe treatment, as well as evaluation of tumor shunting which would result in inadvertent radioactivity delivery to the lungs. In order to evaluate tumor shunting, technetium-99 m labeled macroaggregated albumin (MAA) is injected into the desired hepatic lobar or segmental artery followed by planar/SPECT gamma imaging to determine the fraction of shunting from the liver to the lungs (41).…”
Section: Technical Considerationsmentioning
confidence: 99%